Characterization of an attenuated SARS-CoV-2 variant with a deletion at the S1/S2 junction of the spike protein - Pui Wang; Siu-Ying Lau; Shaofeng Deng; Pin Chen; Bobo Wing-Yee Mok; Anna Jinxia Zhang; Andrew Chak-Yiu Lee; Kwok-Hung Chan; Rachel Chun-Yee Tam; Haoran Xu; Runhong Zhou; Wenjun Song; et al. (Nature Communications, 2021)
The S1/S2 junction of the SARS-CoV-2 Spike protein is emerging as a key factor in virulence and pathogenesis. Here, the authors characterise an attenuated strain of SARS-CoV-2 with deletions in the critical S1/S2 junction and observe enhanced replication, generation of potent adaptive immunity but reduced immunopathology in a hamster model of infection.